Capacity Building and Employee Commitment - Simon Emmanuel Hart (Journal of Advanced Research in Public Policy and Administration, 2024)
This study undertook capacity building and employee commitment. The specific objectives of the study include: identifying the extent to which in-service training influences employee affective commitment; coaching influences employee normative commitment, and mentoring influences employee continuance commitment. Hence, three research questions and three hypotheses guided the study. This study adopted a survey research design. The study was conducted on 30 staff of 10 firms (three3 each) in the hospitality industry from a population of 524 in Rivers State through a simple random sampling technique. The instrument for the data collection is a structured questionnaire called “Manpower Development Strategies and Performance Questionnaires” (MDSPQ) The data obtained through the questionnaire was analysed by mean (x) and standard deviation (SD). Spearman Rank order correlation was used to analyse and test the hypotheses earlier formulated by the researcher. All analyses were imputed on SPSS 22.0. In the cause of the study some capacity building like in-service training, coaching, and mentoring influence employee affective, normative as well and continuance. In the course of the findings it was observed that this method of capacity building according to this paper could be said to be an integral part of the recruitment exercise in that once an employee has been found appointable, it is expected that such an employee need to be positively trained, coached and mentored in line with the vision and aspiration of the organisation for effective discharge of function. Based on the findings of this study, the following recommendations were made for organisational performance, the management of organisations should invest more in in-service training of employees rather than over-turning employees, which causes more confusion in the organisation as the company would keep looking for qualified employees.